Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

A salivary elicitor MsPDI3 from Mythimna separata triggers plant defense responses - Jin-Da Wang; Huan-Tai Lin; Lin Li; Yao-Hui Chen; Ran Wang; Honglin Feng; San-Ji Gao (Insect Biochemistry and Molecular Biology, 2026)

EGCG-functionalized deacetylated konjac glucomannan/carboxylated cellulose nanofiber films: Development, characterization, and application in antibacterial preservation of fresh-cut fruits - Yang Cao; Yile Zhao; Zhixin Li; Di Wu; Chen Chen; Aili Jiang; Xiangzheng Yang; Da Wang; Xian Li; Kunsong Chen (Food Research International, 2026)

Experimental and analytical investigations of composite girders with CSW-CFST chord-UHPC slab under impact loading - Wei Xian; Shuang-Shuang Li; Wen-Da Wang; Yan-Li Shi; Wei-Hong Wu; Wensu Chen (Engineering Structures, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Online monitoring of Maillard reaction dynamics using a custom reaction-transfer device and direct analysis in real time mass spectrometry - Zhichen Qiu; Liping Xu; Xin Geng; Hongli Li; David Da Yong Chen (Food Chemistry, 2026)

Potassium oxalate-activated bamboo charcoal: a green solution for constructing high-performance capacitive deionization electrodes for nitrate removal - Weilong Xiao; Rencheng Li; Ming Gao; Ran Li; Luwei Miao; Yufeng Da; Yang Bao; Ke Li; Tianqi Ao; Qiulin Yang; Xing Chen; Haiyan Mou; et al. (Desalination, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Water release regulating JsSWEET17 transcriptional expression to promote the female flower bud differentiation of Juglans sigillata - Wenwen Li; Da Yuan; Jinyan Chen; Chunxiang Li; Yuanqi Huang; Wen'e Zhang; Xuejun Pan (Journal of Plant Physiology, 2026)

Evolution of PM2.5 chemical composition during summer new particle formation in a coastal city in the yangtze river delta: insights from pollution episodes, machine learning, and air mass origins - Han Zhou; Yichen Lu; Zeyi Li; Honglei Wang; Lijuan Shen; Yue Chen; Deyu Liu; Da Xu (Environmental Research, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Dynamic responses of CFST column to steel beam joints subjected to impact loading - Wei Xian; Wensu Chen; Yan-Li Shi; Wen-Da Wang; Long Zheng; Jun-Liang Yao (Engineering Structures, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Gut Microbiota from Patients with Long COVID Persisting for 2 Years Result in Alterations in Mice that Resemble Post-COVID Symptoms - Daya Zhang; Chen Chen; Yunqian Xie; Shuo Zhou; Da Li; Fan Zeng; Shimei Huang; Yanting Lv; Xianfeng Huang; Fengjiao Mao; Runyu Chen; Ying Mo; et al. (Probiotics and Antimicrobial Proteins, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

How clean is clean enough? Short-chain PFAS remain dominant in treated landfill leachate - Fei Chen; Zhi-Zhong Zhang; Hang Li; Si-Da Meng; Leo W.Y. Yeung; Sakhayana Danilova; Yi-Fan Li; Sheng-Qiang Fan; Zi-Feng Zhang (Journal of Environmental Management, 2026)

Evolution of deep carbonate reservoir parameters under hydro-mechanical coupling - Jing Li; Da Chen; Zhengyang Li; Yuhang Dai; Wenbo Guo; Rui Zheng (Journal of Applied Geophysics, 2026)

Advances in heterogeneous photocatalytic selective oxidation of toluene - Ziqi Dong; Feng Niu; Zeyuan Wu; Zeqi Wu; Junyan Li; Reem H. Alzard; Mohamed Abdellah; Da Chen (Environmental Research, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Regulation of Tph cell differentiation via farnesoid X receptor of dendritic cells in inflammatory bowel disease - Zhen Hu; Minya Liu; Chengkai Zhu; Na Li; Xiaotian Chen; Binlin Da; Yi Li; Chenggong Yu (Inflammation Research, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Study on the relationship between surface deformation and internal fracturing of tunnel surrounding rock under uniaxial loading with multiple blasting disturbances - Tian-Xiao Chen; Shi-Da Xu; Ben-Guo He; Yuan-Hui Li; Jian-Yu Peng (Tunnelling and Underground Space Technology, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

The synergistic recovery of aluminum, lithium and gallium from fly ash using physical enrichment followed by an alkali fusion-organic acid leaching method - Chen Li; Chuncai Zhou; David French; Ian T. Graham; Zixuan Wang; Yunfei Li; Feng Wang; Da Li; Guijian Liu (Minerals Engineering, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Maximizing methane production from food waste: Exploring through integrating Meta-analysis and machine learning - Yingnan Li; Chao Song; Chengning Wang; Da Chen; Chang Chen; Guangqing Liu (Biomass and Bioenergy, 2026)

Correction: Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Synergistic hurdle technology for postharvest preservation of Chinese bayberries: Combining indirect plasma processed air and peracetic acid to reduce chemical dosage - Xiangzheng Yang; Dandan Zheng; Yongrui Ti; Huan Lian; Jiahao Zhong; Da Wang; Chaoyi Shen; Di Wu; Qisen Xiang; Jiangkuo Li; Xian Li; Kunsong Chen (Food Chemistry, 2026)

Preparation of polybutylene adipate terephthalate-based degradable nanofibrous membranes loaded with metal-organic frameworks for linear and sustained release of thymol via microfluidic blown spinning for fruit preservation - Feifei Wang; Xiaohong Guo; Wenjing Shi; Xiangju Feng; Yongrui Ti; Xiangzheng Yang; Da Wang; Jiangkuo Li; Zhiqiang Wang; Zhengan Yang; Di Wu; Kunsong Chen (Food Packaging and Shelf Life, 2026)

Dual-functional Ti-MOF/g-C3N4 engineered PVDF membranes for photocatalytic self-cleaning and high-flux water remediation - Dongyuan Li; Xiaojun Peng; Rui Zhang; Yadong Chen; Peng Song; Wei Chen; Da Wang (Environmental Research, 2026)

Aged nanoplastics exacerbate CPPD-induced ocular toxicity via the thyroxine pathway in zebrafish - Jin Li; Yi Zheng; Yuying Yin; Wenda Gao; Fan Tang; Xinlin Zhao; Qi Xin; Suiyi Liu; Jiaqi Xiong; Jian Lin; Da Sun; Jiangfei Chen (Aquatic Toxicology, 2026)

Dual Low-b-value-driven U-shaped fusion GAN for synthesizing high-b-value prostate DWI - Rui Feng; Qun Huang; Aiping Chen; Chuanbing Wang; Leilei Zhou; Jingjing Xu; Xiaodong Wang; Da Cao; Xiuhan Li; Wei Wang (Physical and Engineering Sciences in Medicine, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Self-catalyzed NiFe foam anode fabricated via tape-casting for oxygen evolution reaction in anion exchange membrane water electrolysis - Li-Da Chiu; Calvin Leo Putra; Shuo-En Yu; I-Chung Cheng; I-Chih Ni; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Fuel, 2026)

Dual-salt template synthesis of coal tar pitch-based porous carbon for capacitive deionization of NH4+ and NO3− - Ke Li; Luwei Miao; Weilong Xiao; Rencheng Li; Yang Bao; Yufeng Da; Xurui An; Qiulin Yang; Wenqing Chen (Desalination, 2026)

Engineering pore structure of bamboo-derived porous carbons via pyrolysis behavior of various organic potassium salts for efficient nitrate removal by capacitive deionization - Rencheng Li; Menghan Pu; Weilong Xiao; Yufeng Da; Luwei Miao; Yang Bao; Ke Li; Qiulin Yang; Wenqing Chen; Hui Sun (Desalination, 2026)

An improved depth-averaged landslide dam breach model with modified sediment transport and bank collapse algorithms - Jiheng Li; Wei Shen; Da Huang; Xilin Xia; Jian Guo; Denghai Liu; Jianchao Chen; Tonglu Li; Jianbing Peng (Computers and Geotechnics, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

A CNN-LSTM-Attention model for risk prediction of offshore wind turbines - Jia-Xuan Li; Da-Gang Lu; Jia-Wei Ding; Yong Ding; Hao Liu; Libo Chen; Wenbing Wu (Ocean Engineering, 2026)

Design, fabrication and multiple failure behavior of carbon fiber composite circumferential corrugated reinforced cylindrical shells under hydrostatic pressure - Yang-Xu Chong; Jin-Shui Yang; Da-Long Ding; Fang Yang; Hai-Dong Li; Yu-Yin Wei; Er Zhang; Jia-Dong Zeng; Guo-Tao Chen (Ocean Engineering, 2026)

Seasonal fate and removal of per- and polyfluoroalkyl substances in a wastewater treatment plant with a Bacillus bio-reactor - Sakhayana Nikolaevna Danilova; Si-Da Meng; Fei Chen; Zhi-Zhong Zhang; Bing-Feng Liu; Vasiliy Egorovich Kolodeznikov; Natalia Nikolaevna Petrova; Yi-Fan Li; Zi-Feng Zhang (Journal of Water Process Engineering, 2026)

Novel kinked connection component (KCC) for enhanced progressive collapse performance in CFST column–steel beam joints - Long Zheng; Yu-Chen Zhang; Yan-Li Shi; Wen-Da Wang; Yin-Quan Yu (Engineering Structures, 2026)

Mechanoadaptive conductive hydrogels with dual functionalities for epidermal sEMG monitoring and diabetic wound healing - Guoqiang Ren; Jingyun Ma; Qiuyue Peng; Pengfei Liu; Xiaobo Wang; Da Li; Yuesheng Zhang; Chaonan He; Chen Huang; Honghua Ye; Yavuz Nuri Ertas; Qingbo Xu; et al. (Chemical Engineering Journal, 2026)

Multi-objective decision model for wastewater treatment technology selection based on machine learning - Yanbo Liu; Zhaohan Zhang; Xinyi Chen; Guohong Liu; Da Li; Jiannan Li; Yanfang Song; Jinhao Duan; Kuokai Sun; Yujie Feng (Bioresource Technology, 2026)

Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Whole-genome Resequencing Reveals the Sex Determination System and Develops a Sex-specific Marker in Fat Greenling (Hexagrammos otakii) - Duan Liao; Yangqing Zhang; Chunlong Miao; Shuo Li; Weijing Li; Chen Li; Ivana Felipe da Rosa; Lucas Benites Doretto; Yuyan Liu; Qian Wang; Kaiqiang Liu; Hong-Yan Wang; et al. (Marine Biotechnology, 2026)

A Real-World Disproportionality Analysis of Drug-Induced Heart Failure: Integrating FAERS Database and AHA Statement - Da Li; Yidan Dong; Lei Yao; Xiaozhe Chen; Yunfeng Li; Xiaohong Deng; Jianhua Li; Mingzhu Wang; Deyu Fu (Cardiovascular Toxicology, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Survey of volatile organic compounds released at different temperatures from tea by direct analysis in real time mass spectrometry - Xin Geng; Zhichen Qiu; Chunyu Zhang; Hongli Li; David Da Yong Chen (Food Chemistry, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

A mid‐Proterozoic coupled Sr and Li isotope excursion and its potential connection to enhanced weathering and ocean oxygenation at 1.57 Ga - Xi Chen; Ying Zhou; Simon W. Poulton; Fred T. Bowyer; Colin Mettam; Shihong Zhang; Maoyan Zhu; Da Li; Philip A.E. Pogge von Strandmann; Benjamin J.W. Mills; Graham A. Shields (Earth and Planetary Science Letters, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

Evaluation of residual virulence and protective efficacy for Brucella melitensis vaccine strain M5-90 in mice and guinea pigs - Chenchen Lu; Chenglan Zhang; Yanan Li; Zujian Qiao; Xijun Wang; Weiye Chen; Xiaoyi Chen; Qian Jiang; Da Xu; Zhigao Bu; Sen Hu (Veterinary Microbiology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unlocking inherent superoxide production from potassium peroxoborate for efficient PAHs degradation - Jiajie Zhou; Shaohong Wang; Yan Tian; Yingqi Wang; Guohong Liu; Da Li; Tongtong Liu; Dahong Chen; Yujie Feng (Journal of Hazardous Materials, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

Experimental and analytical investigation on continuous two-span RC beams flexural strengthened with aluminum alloy bars - Xu Chen; Guohua Xing; Yakun Li; Jun Zhang; Da Luo; Zhaoqun Chang; Boquan Liu; Haonan Wang (Engineering Structures, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Synthesis, evaluation and preliminary clinical study of novel 68Ga-labeled Nectin-4 targeting PET tracer - Geng Hu; Zexin Xu; Da-Yong Hou; Pengcheng Ran; Liang Cheng; Wei Liu; Yue Zhao; Fan Jia; Xinyue Yang; Huihui You; Baoyuan Li; Hongxin Li; et al. (Chemical Engineering Journal, 2026)

Methylation in ambient ion source enables direct isomer differentiation of oligosaccharides by tandem mass spectrometry - Liping Xu; Dandan Sha; Rongfan Ren; Hongli Li; David Da Yong Chen (Carbohydrate Polymers, 2026)

FCMI analysis of multiphysics coupling of fuel rods at the end of cycle of Xi’an pulsed reactor - Zhaohao Wang; Jinkai Zhang; Tianliang Hu; Di Yun; Duoyu Jiang; Da Li; Lixin Chen; Wenbo Liu (Annals of Nuclear Energy, 2026)

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

Multi-objective optimization study of wave elimination and electricity generation performance of Savonius hydrokinetic turbine array based on metamodel - Ruiyin Song; Haihan Yu; Congjie Ren; Xi Cui; Fengshen Li; Lei Zhang; Gao Bai; Kai Chen; Da Liu (Ocean Engineering, 2026)

Applying Interpretable Machine Learning for Hypoxia Mitigation: an Operational Framework Coupling Predictive Modeling and Causal Inference for Urban River Management - Jia-yun Chen; Da-wei Wang; Zu-lin Hua; Ke-jian Chu; Li Gu (Water Resources Management, 2026)

The Combination of Sodium Tanshinone IIA Sulfonate and Mesenchymal Stem Cell-derived Exosomes Against Spinal Cord Injury via VEGF Pathway - Dan Luo; Lin Ma; Zhijian Pan; Ling Chen; Zhifeng Hu; Chaolun Liang; Zenglu Wang; Zhifeng Xiao; Dingkun Lin; Jinfeng Li; Da Guo; Xing Li (Molecular Neurobiology, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

Effect of lipid oxidation on the color deterioration of ready-to-eat oysters: Discussion based on the model system - Ying Luo; Jie Xu; Ying-Chen Fan; Zong-Han Wang; Yuan-Yuan Hu; De-Yang Li; Yu-Xin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Preparation of ZnSO4 cross-linked double-network hydrogels via synergistic ionic and Hofmeister effects as in-situ fruit packaging integrating cushioning and monitoring - Wenjun Wu; Jiahao Zhong; Zhichao Yang; Ziqiang Qin; Chaoyi Shen; Zihan Cai; Xiangzheng Yang; Qilei Li; Da Wang; Jiangkuo Li; Xian Li; Di Wu; et al. (Food Packaging and Shelf Life, 2025)

Myocardial-targeted mitochondria attenuate ischemic/reperfusion injury by reprogramming oxidative phosphorylation and modulating pyroptosis - Xi Li; Maodi Xie; Da Zhu; Qinqin He; Guo Chen; Zhongxiu Chen; Qian Li; Tao Li (Chemical Engineering Journal, 2025)

Dynamic 3-hydroxyflavone-modified D-alanine nanoparticles for metabolic-incorporation in anaerobic, pathogenic biofilms generating CO in infected periodontal pockets - Da-Yuan Wang; Jing Li; Xiao-Han Tian; Siyu Zhang; Yao Chen; Feihe Ma; Henk.J. Busscher; Jing Shen; Linqi Shi (Chemical Engineering Journal, 2025)

Research and application of CMA numerical weather prediction in meteorological support for the Beijing Winter Olympics (2022) - Guo Deng; Xueshun Shen; Huiling Yuan; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Mingxuan Chen; Jianjie Wang; et al. (Science China Earth Sciences, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Analysis of the Volatile Aroma Components in ‘Yuguan’ Apple Fruit by Gas Chromatography–Mass Spectrometry - Xin Liu; Da Zhang; Jie Li; Dongmei Chen; Chaohong Zhang; Guodong Zhao; Linguang Jia; Han Wang; Xumin Wang; Tongsheng Zhao; Xinsheng Zhang (Applied Fruit Science, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Divergent drought-induced suppression on vegetation and associated feedbacks: Satellite-based observations in 2022 across the Yangtze River basin, China - Lei Han; Yanan Chen; Chaoyang Wu; Li Yao; Ying Wang; Chao Su; Xuan Li; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Xuguang Tang (Journal of Hydrology, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Ru8@NU-1000 as difunctional photocatalysts for visible-light-driven efficient CO2 reduction integrated with furfurylamine oxidation - Jiayi Zhang; Yanan Qu; Kang Bu; Jingting Lu; Da Chen; Huafeng Li; Liqun Bai (Fuel, 2025)

Experimental and analytical investigations of prefabricated RC beam to CFST column joints subjected to beam-end impact loads - Wei Xian; Zhi-Meng Wang; Wensu Chen; Yan-Li Shi; Wen-Da Wang (Engineering Structures, 2025)

Siloxene coupled graphene anode membrane with Zn-ion intercalation for all-solid-state Zn-ion hybrid supercapacitors - Erhui Zhang; Da Xie; Yuchen Hong; Zhenzhen Hui; Yongsheng Zhou; Shengbiao Zheng; Jiahao Guo; Zirong Li; Jie Chen; Jing Tang (Chemical Engineering Journal, 2025)

ULK1-dependent phosphorylation of OGT instructs the tumorigenicity of O-GlcNAcylation - Zhuan Lv; Qingen Da; Yumiao Li; Aiyun Yuan; Guangcan Shao; Xiaoxuan Lu; Yue Wang; Xuefang Zhang; Jingjing Liu; Meng-Qiu Dong; Yuanyuan Ruan; Chen Wu; et al. (Science China Life Sciences, 2025)

Hierarchical Replay of Multi-regional Sequential Spiking Associated with Working Memory - Ermeng Huang; Da Xu; Huangao Zhu; Zhaoqin Chen; Yulei Chen; Shujun Lei; Jiawei Liu; Chengyu T. Li; Xiaoxing Zhang (Neuroscience Bulletin, 2025)
How do millisecond-scale neural activities mediate second-scale behaviors? We recorded brain-wide activity in mice performing an olfactory working-memory task to decipher the cross-region organization of activity. Spike-correlograms analysis revealed millisecond within- and cross-region spike couplings, which were enriched among memory-encoding neurons with similar odor preferences. Spike coupling linked neurons into motifs of chains, single loops, and nested loops, especially among hippocampal and prefrontal-cortex neurons. Spike-coupling direction and activity-chain propagation aligned with that of memory-associated activity waves. Intriguingly, activity motifs were replayed before and after task performance, and during inter-trial intervals. Motifs exhibited hierarchical organization, with progressively longer time constants and the number of participating neurons. Thus, hierarchically organized and replayed cross-region spiking motifs are modulated on demand during the delay period, providing a potential mechanism for perceptual working-memory maintenance.

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Raffinose esters of long-chain unsaturated fatty acids: Preparation, characterization, and in vitro digestive behavior - Da Ma; Anjie Li; Mengfei Xie; David Julian McClements; Jing Chen (Food Research International, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Machine learning and causal inference for disentangling air pollution reduction during the Asian Games in megacity Hangzhou - Fan Zhang; Renchang Yan; Xianman Ye; Luolan Fei; Yaofu Zhu; Xiyao Chen; Shupeng Zhu; Bing Qi; Da Xu; Weijun Li (Environmental Pollution, 2025)

Mechanical response of tunnel surrounding rock under blasting disturbance with different stress conditions based on acoustic emission and digital image correlation - Tian-xiao Chen; Shi-da Xu; Ben-guo He; Yuan-hui Li; Han Lei (Engineering Geology, 2025)

BiOI/ZIF-8 Z-scheme heterojunction enhance TCH degradation under anoxic environment - Kang Bu; Yanan Qu; Jiayi Zhang; Tingya Zhang; Leyu Wu; Da Chen; Shiliang Heng; Huafeng Li; Liqun Bai (Chemical Engineering Journal, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Insight into the effect of manganese oxidation state on the synthesis of ethylene urea from CO2 and ethylenediamine - Fei Wang; Biao Da; Yulong Jin; Piracha Sanwal; Lei Cui; Siru Chen; Jie Xu; Bing Xue; Gao Li (Journal of Environmental Sciences, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Dynamic Characteristics and Energy Dissipation Laws of Reinforced Porous Coral Reef Limestone - Da Mei; Xiaoqing Wei; Yi Luo; Shangyuan Chen; Xinping Li; Junhong Huang; Chunneng Yang (Rock Mechanics and Rock Engineering, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Controlling high-concentration precursor crystallization to minimize photon loss in bifacial perovskite solar cells - Shan Gan; Haoxuan Sun; Min Wang; Da Dou; Siyang Zhang; Chen Li; Liang Li (Science Bulletin, 2025)

Efficient catalytic degradation and detoxification of 6PPD-quinone by the multifunctional enzyme system of phanerochaete chrysosporium - Haiyang Yu; Li Luo; Baihui Wu; Jiaxuan He; Hanbing Wang; Rongbing Chen; Mingxia Ji; Qinsi Yang; Guoming Zeng; Wei Wu; Da Sun (Journal of Hazardous Materials, 2025)

The Effect of Triethanolamine Dodecylbenzene Sulfonate on Metastable Corrosion of 304 Stainless Steel - Yingdi Liao; Huan Zhang; Xin Wang; Li Chen; Chenggeng Huang; Yazhou Zhao; Bo Da (Journal of Ocean University of China, 2025)

Integrating synergistic effects of biodiversity conservation and ecosystem services into nature conservation strategies - Luu Van Thong Trac; Da-Li Lin; Chen-Fa Wu (Journal of Environmental Management, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

BikeshareGAN: Predicting dockless bike-sharing demand based on satellite image - Yalei Zhu; Yuankai Wang; Junxuan Li; Qiwei Song; Da Chen; Waishan Qiu (Journal of Transport Geography, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Unveiling novel oxygen-dependent docosahexaenoic acid biosynthesis pathway in Crypthecodinium cohnii via dual-function △4-fatty acid desaturases - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Bioresource Technology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

IGF2BPs-regulated TIN2 confers the malignant biological behaviors of gastric cancer cells - Fang Li; Yadong Zhou; Zhiming Liao; Da Huang; Ziqing Zhang; Guoqun Chen (Tissue and Cell, 2025)

Dynamic stiffness of full-scale damaged polyester mooring ropes - Yushun Lian; Yongyue Xie; Jinhai Zheng; Wenxing Chen; Da Li; Shichang Chen; Jisheng Zhang; Xiang Wu; Jiaoxue Shi; Solomon C. Yim (Ocean Engineering, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Histological and transcriptome analysis of gonadal development provides new insights into the characteristics of sex differentiation and the screening of key genes in the golden pompano (Trachinotus blochii) - Feibiao Song; Huan Liang; Zhi Li; Da Zheng; Huapeng Chen; Xinxin Wang; Chaoyue Deng; Wenyan Lin; Changlin Chen; Junlong Sun; Li Zhou; Jian Luo (Aquaculture, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Functional microorganisms in hydrogen production: Mechanisms and applications - Yonghong Fan; Feiran Zhang; Kun He; Dan Yu; Haoming Chen; Da Tian; Yixiao Shi; Zhen Li; Xiaomei Wang (Bioresource Technology, 2025)

Toxesbium gen. nov., the first definitive member of Ernobiinae from mid-Cretaceous amber of northern Myanmar (Coleoptera: Ptinidae) - Yan-Da Li; T. Keith Philips; Di-Ying Huang; Chen-Yang Cai (PalZ, 2025)

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Treatment of dye-containing wastewater using discarded animal blood-derived hemoglobin crystals - Xiao-Qian Jin; Jie Liu; Chen-Yuan Li; Liang-Liang Chen; Jia-Lei Li; Xue-Ting Wang; Guang-Ming Mi; Da-Chuan Yin (Journal of Environmental Management, 2025)

Exploring the impact of land use on bird diversity in high-density urban areas using explainable machine learning models - Xiangyi Li; Zhaoxi Wang; Yu Chen; Zhengwu Wang; Da Kuang (Journal of Environmental Management, 2025)

Dual carbon isotopes constrain the sources and age variations of terrestrial organic carbon in the middle Okinawa Trough since the last deglaciation - Mengna Chen; Chenglong Su; Shuang Wang; Da-Wei Li; Hailong Zhang; Li Li; Guangxue Li; Bingyuan Xu; Jishang Xu; Meixun Zhao (Global and Planetary Change, 2025)

Enhancing whipped cream anti-freeze properties: A dual plant system with aquafaba and mung bean protein - Yan Zhan; Lai Wei; Tianai Ge; Da Chen; Li Wang; Jiang Jiang (Food Hydrocolloids, 2025)

Microbial electrochemical coupling floating treatment wetland enhanced low-carbon wastewater remediation: Driving wastewater denitrification with different current densities - Zhengyu Yan; Guohong Liu; Ye Qiu; Dongyi Li; Dahong Chen; Da Li; Yujie Feng (Chemical Engineering Journal, 2025)

Fraxetin inhibits IKKβ, blocks NF-κB pathway and NLRP3 inflammasome activation, and alleviates spleen injury in sepsis - Liwei Huangfu; Jing Wang; Da Li; Haiyang Fei; Xuan Chen; Jingquan Dong; Lan Sun (Chemico-Biological Interactions, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Steady-state analysis of Xi’an Pulse Reactor based on the multi-physics coupling method - Tianliang Hu; Duoyu Jiang; Xinyi Zhang; Zhaohao Wang; Lipeng Wang; Lu Cao; Da Li; Lixin Chen (Annals of Nuclear Energy, 2025)

Declining trends and regional variations of organophosphate ester contamination in indoor dust from mainland China: Insights from a filed study and meta-analysis - Jing Li; Liu Yang; Yuying Ding; Fei Yang; Hongli Tan; Shuqin Tang; Da Chen (Science of The Total Environment, 2025)

Targeted isolation of lignans from the roots of Anthriscus sylvestris (L.) Hoffm. by small molecule accurate recognition technology - Yan-ling Liu; Yan-gang Cao; Ya-juan Zheng; Ying Niu; Lan Chen; Xu Chen; Xin-yi Ma; Xiang-da Li; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Extraction of antimicrobial peptides from pea protein hydrolysates by sulfonic acid functionalized biochar - Min Liu; Xian-Da Hu; Xiang-Yu Huang; Li Wen; Zhou Xu; Li Ding; Yun-Hui Cheng; Mao-Long Chen (Food Chemistry, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Remediation of heavy metal contaminated soil in mining areas with vaterite-type biological calcium carbonate - Jun-li Chen; Chang-xiong Zou; Wei-da Wang; Chun-li Zheng; Qing-hong Jiang; Zhe Wang (Process Safety and Environmental Protection, 2024)

Experimental and numerical investigation of dynamic characteristics and safe mooring criteria of moored outfitting ships under swell conditions - Yunpeng Zhu; Xiaojun Li; Yan Zhu; Ming Wen; Hulin Chen; Xiaotong Yu; Da Chen (Ocean Engineering, 2024)

Experimental study on wave energy harvesting from a coastal resonant water tank - Shing-Nan Wu; Yun-Da Sin; Po-Hung Yeh; Li-Quan Xie; Bang-Fuh Chen (Ocean Engineering, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Enhanced biofouling resistance of polyvinylidene fluoride ultrafiltration membranes using crayfish shell biochar with calcium species - Dawei Zhang; Liqing Ma; Yuewu Da; Weiying Li; Meijuan Chen; Kan Hu; Xiangzhou Meng; Yao Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2024)

Microfluidic-blow-spinning of carvacrol-loaded porphyrin metal − organic framework nanofiber films with synergistic antibacterial capabilities for food packaging - Zi-An Deng; Menglu Wu; Chaoyi Shen; Xiangzheng Yang; Da Wang; Jiangkuo Li; Di Wu; Kunsong Chen (Food Chemistry, 2024)

Deacetylated konjac glucomannan films functionalised with carboxylated cellulose nanofiber and anti-browning components for fresh-cut apple preservation - Yile Zhao; Zheng Wu; Chen Chen; Olaniyi Amos Fawole; Aili Jiang; Xiangzheng Yang; Da Wang; Xian Li; Di Wu; Kunsong Chen (Food Packaging and Shelf Life, 2024)

Insights into the accumulation and hepatobiliary transport of bisphenols (BPs) in liver and bile - Jie Ding; Ying Liu; Yanjie Li; Yongheng Huang; Shibo Li; Fei Wang; Da Chen; Bin Lu; Nan Lin (Environmental Research, 2024)

Sample-to-answer point-of-care testing platform for quantitative detection of small molecules in blood using a smartphone-and microfluidic-based nanoplasmonic biosensor - Hongli Fan; Rui Li; Youqian Chen; Qiang Da; Chenchen Xiong; Yiyi Zhang; Zhiguo Qin; Gang L. Liu; Liping Huang (Chemical Engineering Journal, 2024)

A Comparative Proteomics Study Revealing the Impact of Growing Region and Cultivar on Protein Expression in the Leaves of Nicotiana tabacum Plants - Yongxu Hu; Min Chen; Gang Li; Da Wu; Xiangmin Zhang (Plant Molecular Biology Reporter, 2024)

Shoot Organogenesis from Tetrastigma hemsleyanum Leaf and Petiole Explants, and Subsequent Plant Regeneration and Acclimatization - Jinhui Pang; Yuping Xiong; Yujie Zeng; Xiaohong Chen; Jianrong Li; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (Journal of Plant Growth Regulation, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

Centrifugated lateral flow assay strips based on dual-emission carbon dots modified with europium ions for ratiometric determination and on-site discrimination of tetracyclines in environment - Houwen Hu; Haoming Xing; Yihao Zhang; Xinru Liu; Sineng Gao; Linfan Wang; Tingting Li; Ting Zhang; Da Chen (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

The effect of lambda-cyhalothrin nanocapsules on the gut microbial communities and immune response of the bee elucidates the potential environmental impact of emerging nanopesticides - Dezheng Guo; Zhongyu Li; Yiwen Zhang; Wei Zhang; Chen Wang; Da-xia Zhang; Feng Liu; Zheng Gao; Baohua Xu; Ningxin Wang (Journal of Hazardous Materials, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Functionalized porphyrin as a carrier bridge and a passivator for perovskite solar cells - Longchen Tao; Haitao Zhang; Xinyu Zhu; Chenhan Qi; Tianhong Ye; Niping Chen; Lixin Xiao; Baojun Li; Xufei Sun; Da-Qin Yun; Lingling Zheng (Chemical Engineering Journal, 2024)

Synergistic ultra-high adsorption and oxidation of arsenic in groundwater by iron-modified biochar: Mechanisms and potential application - Jing Wei; Lina Wang; Yihan Liu; Da Ding; Qun Li; Yousheng Liu; Yun Chen; Meng Mao; Shaopo Deng (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Ambient mass spectrometry imaging of food natural products by angled direct analysis in real time high-resolution mass spectrometry - Zhiru Bai; Zhengyan Zhao; Saiting Wang; Hongli Li; David Da Yong Chen (Food Chemistry, 2024)

Dynamic performance of fiber-reinforced ultra-high toughness cementitious composites: A comprehensive review from materials to structural applications - Liangming Sun; Shuguang Liu; Hanbing Zhao; Umar Muhammad; Da Chen; Wengui Li (Engineering Structures, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Development of a solidification blockage discriminant model in filling pipelines - Chen Zeng; Cong Shen; Maolong Liu; Xiaoyan Tian; Da Li; Limin Liu; Hanyang Gu (Annals of Nuclear Energy, 2024)

Multi-dimensional signals coupling of simultaneous acquisition stripping current with laser-induced breakdown spectroscopy for accurate analysis of Cd(II) in coexisting Cu(II) - Yuan-Fan Yang; Zong-Yin Song; Zi-Hao Liu; Zhi-Wei Gao; Xin Cai; Cong-Cong Huang; Pang-Da Dai; Meng Yang; Pei-Hua Li; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Research on pollution identification and safety thresholds based on the olfactory effect on a halogenated hydrocarbon contaminated site - Xuwei Li; Wenyi Xie; Ya Zhang; Yun Chen; Mei Li; Lingya Kong; Da Ding; Shaopo Deng (Chemosphere, 2024)

Deviation entropy-based dynamic multi-model ensemble interval prediction method for quantifying uncertainty of building cooling load - Changcheng Chen; Jingjing An; Xin Zhou; Chuang Wang; Han Li; Da Yan (Energy and Buildings, 2024)

Understanding the structural relation and electrochemical evolution between ZnGeP2 and ZnSiP2 twin phosphides for advanced Li-ion batteries - Wei Liang; Bin Chen; Da Li; Xuhao Liu; De Li; Xuan Tian; Panpan Zhang; Xing Lu; Yaqing Wei; Yong Chen (Chemical Engineering Journal, 2024)

Magnéli Ti4O7 nanowire induces locally enhanced electric field and electrocatalytic activity for rapid and efficient water disinfection via synergistic electroporation and electrochlorination - Jun-Wen Li; Gen-Qiang Chen; Hai-Ming Wu; Da Chen; Hai Liu (Chemical Engineering Journal, 2024)

Continuous deposition of pre-aged organic carbon in the southern Mariana Trench since the last deglaciation - Da-Wei Li; Mengna Chen; Shuai Liu; Hailong Zhang; Zicheng Wang; Xiaoyan Ning; Jiwei Tian; Meixun Zhao (Chemical Geology, 2024)

Metformin modulates mitochondrial autophagy in renal tubular epithelial injury induced by high glucose via the Keap1/Nrf2 pathway - Da Sun; Huimin Li; Yinke Du; Ying Chen; Li Yao; Lining Wang (Molecular and Cellular Biochemistry, 2024)

The effects of an online food waste reduction platform in university canteens in Wuhan, China - Wanqi Du; Li Xue; Da Xu; Hui Zhang; Gang Liu; Huabo Duan; Junjie Dong; Jinyi Chen; Huali Zhang (Journal of Cleaner Production, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Application of phosphogypsum and phosphate-solubilizing fungi to Pb remediation: From simulation to in vivo incubation - Lingzi Meng; Kejin Ding; Yige Qiu; Yunhui Chen; Hongxun Huo; Dan Yu; Da Tian; Zhen Li (Science of The Total Environment, 2024)

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

Effects of abamectin nanocapsules on bees through host physiology, immune function, and gut microbiome - Dezheng Guo; Ying Wang; Zhongyu Li; Da-xia Zhang; Chen Wang; Hongfang Wang; Zhenguo Liu; Feng Liu; Xingqi Guo; Ningxin Wang; Baohua Xu; Zheng Gao (Science of The Total Environment, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Estimation of the suspended sediment concentration in ice-covered channels based on the gravitational theory - Wenxin Huai; Hailiang Chen; Zhonghua Yang; Da Li; Feifei Wang (Journal of Hydrology, 2024)

Ultrasound synergistic iron-nitrogen biocarbon activated persulfate to ofloxacin degradation - Jun Chen; Zongsheng Zhan; Zhaoming Chen; Yutong Wang; Xue Li; Mingxia Du; Dawei Teng; Dong Lv; Chunnian Da; Mengqiu Xu (Journal of Environmental Chemical Engineering, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Rotavirus infection inhibits SLA-I expression on the cell surface by degrading β2 M via ERAD-proteasome pathway - Zhaoyang Jing; Ling Wu; Yudi Pan; Liaoyuan Zhang; Xin Zhang; Da Shi; Hongyan Shi; Jianfei Chen; Zhaoyang Ji; Jiyu Zhang; Tingshuai Feng; Jin Tian; et al. (Veterinary Microbiology, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

Potassium peroxoborate: A sustained-released reactive oxygen carrier with enhanced PAHs contaminated soil remediation performance - Jiajie Zhou; Yan Tian; Chen Yan; Da Li; Tongtong Liu; Guohong Liu; Dahong Chen; Yujie Feng (Journal of Hazardous Materials, 2024)

Distribution of per- and polyfluoroalkyl substances in blood, serum, and urine of patients with liver cancer and associations with liver function biomarkers - Cao Dai; Lin Peng; Yanjie Li; Zhendong Li; Da Chen; Fei Wang; Nan Lin (Journal of Environmental Sciences, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

Low-frequency Stimulation at the Subiculum Prevents Extensive Secondary Epileptogenesis in Temporal Lobe Epilepsy - Yujia Shen; Yiwei Gong; Xiaoli Da; Shajing Gao; Shuo Zhang; Minjuan Sun; Yuanzhi Yang; Xiaoyun Qiu; Menghan Li; Yang Zheng; Fan Fei; Yi Wang; et al. (Neuroscience Bulletin, 2024)

Scientific Advances and Weather Services of the China Meteorological Administration’s National Forecasting Systems during the Beijing 2022 Winter Olympics - Guo Deng; Xueshun Shen; Jun Du; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Jiangkai Hu; Jianjie Wang; et al. (Advances in Atmospheric Sciences, 2024)

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Effect of liver cancer on the accumulation and hepatobiliary transport of per- and polyfluoroalkyl substances - Ying Liu; Lin Peng; Yanjie Li; Xingwen Lu; Fei Wang; Da Chen; Nan Lin (Journal of Hazardous Materials, 2024)

Can we redevelop ammonia nitrogen contaminated sites without remediation? The key role of subsurface pH in human health risk assessment - Da Ding; Yun Chen; Xuwei Li; Qiang Chen; Lingya Kong; Rongrong Ying; Lei Wang; Jing Wei; Dengdeng Jiang; Shaopo Deng (Journal of Hazardous Materials, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Binary Li/Na tungstates modified Mg6MnO8 as redox catalysts for enhanced performance of chemical looping oxidative dehydrogenation of ethane - Haitao Chen; Zifan Xing; Da Song; Xiang Yu; Yang Li; Fang He (Chemical Engineering Journal, 2024)

Bacoside a inhibits the growth of glioma by promoting apoptosis and autophagy in U251 and U87 cells - Hai-Yun Liu; Yu-Long Ji; Hong Du; Shu-Hui Chen; Da-Peng Wang; Qiao-Li Lv (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

OPEs-ID: A software for non-targeted screening of organophosphate esters based on liquid chromatography-high-resolution mass spectrometry - Yinran Xiong; Jinyue Liu; Jing Yu; Da Chen; Tiantian Li; Fengli Zhou; Ting Wu; Xiaotu Liu; Yiping Du (Journal of Hazardous Materials, 2024)

Transplacental transport of per- and polyfluoroalkyl substances (PFAS): Mechanism exploration via BeWo cell monolayer model - Hexia Chen; Shuchao Wei; Jing Li; Zheng Zhong; Da Chen (Journal of Hazardous Materials, 2024)

Behavior of eccentrically loaded rectangular CFST components for shear walls using double horizontally-corrugated steel plates - Xu Liao; Xian Li; Sheng-Da Zhao; Chen Yang; Dong-Dong Yin (Engineering Structures, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

High-performance pulse light stable perovskite indoor photovoltaics - Chen Li; Haoxuan Sun; Min Wang; Shan Gan; Da Dou; Liang Li (Science Bulletin, 2024)

Quantification of perfluorinated compounds in atmospheric particulate shows potential connection with environmental event - Hua Tang; Ying Wang; Shengling Si; Hongli Li; David Da Yong Chen (Journal of Environmental Sciences, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Carboxymethyl chitosan and polycaprolactone-based rapid in-situ packaging for fruit preservation by solution blow spinning - Chaoyi Shen; Xiangzheng Yang; Da Wang; Jiangkuo Li; Changqing Zhu; Di Wu; Kunsong Chen (Carbohydrate Polymers, 2024)

Effects of Fe/Fe–Mn oxides loaded biochar on anaerobic degradation of typical phenolic compounds in coal gasification wastewater: Performance and mechanism - Da Li; Qinxue Wen; Zhiqiang Chen (Bioresource Technology, 2024)

Performance and mechanism of pilot-scale carbon fibers enhanced ecological floating beds for urban tail water treatment in optimized ecological floating beds water surface coverage - Zhengyu Yan; Dahong Chen; Ye Qiu; Dongyi Li; Chen Yan; Jiannan Li; Da Li; Guohong Liu; Yujie Feng (Bioresource Technology, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Bell pepper derived nitrogen-doped carbon dots as a pH-modulated fluorescence switching sensor with high sensitivity for visual sensing of 4-nitrophenol - Guoqiang Guo; Tingting Li; Ziyi Liu; Xinyu Luo; Ting Zhang; Siyuan Tang; Xu Wang; Da Chen (Food Chemistry, 2024)

Application of urea-based magnetic covalent organic framework as sorbent for the determination of coumarin and its derivatives in food samples combined with liquid chromatography-mass spectrometry - Xue-Mei Nie; Yin-Long Li; Xiu-Li Xu; Feng-Ming Chen; Feng Zhang; Da Chen (Food Chemistry, 2024)

Construction of Rh-N4 single atoms and Rh clusters dual-active sites for synergistic heterogeneous hydroformylation of olefins with ultra-high turnover frequency - Da Yang; Shu Tao; Houyu Zhu; Zhidong Wang; Wenwen Gao; Jinggang Yu; Minmin Wang; Guangxun Sun; Junxi Li; Hsiao-Chien Chen; Bin Liu; Yongming Chai; et al. (Chemical Engineering Journal, 2024)

From Acupoints to Mylohyoid: Revealing the Neural Circuitry Basis of Electroacupuncture for Dysphagia - Xiaoli Da; Xuhong Jiang; Lihong Li; Cenglin Xu; Zhong Chen (Neuroscience Bulletin, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Study on the performance of Anerinibacillus sp. in degrading cyanide wastewater and its metabolic mechanism - Yao-ting Duan; Wei-da Wang; Si-yuan Qin; Xin Xu; Bo-xi Li; Min-jie Chen; Chun-li Zheng (Chemosphere, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

Construction of fluorescent sensor array and three-dimensional microfluidic paper based analytical device for specific identification and visual determination of antibiotics in food - Tingting Li; Guoqiang Guo; Haoming Xing; Siyuan Tang; Houwen Hu; Linfan Wang; Xiaoqing Qian; Da Chen (Food Chemistry, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Gametophyte Development and Sporophyte Regeneration of Alsophila spinulosa - Yuping Xiong; Yujie Zeng; Junyu Liu; Xiaohong Chen; Yuan Li; Xinhua Zhang; Zhan Bian; Jaime A. Teixeira da Silva; Songjun Zeng; Kunlin Wu; Guohua Ma (Journal of Plant Growth Regulation, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Enhanced anaerobic biodegradation of typical phenolic compounds in coal gasification wastewater (CGW) using biochar: Focusing on the hydrolysis-acidification process and microbial community succession - Da Li; Qinxue Wen; Zhiqiang Chen (Environmental Research, 2023)

Metagenomics insights into high-rate nitrogen removal from municipal wastewater by integrated nitrification, partial denitrification and Anammox at an extremely short hydraulic retention time - Junjiang Chen; Xiaonong Zhang; Li Zhou; Zixuan Zhu; Zhiqiang Wu; Kangyu Zhang; Yiwen Wang; Ting Ju; Xu Ji; Da Jin; Peng Wu; Xingxing Zhang (Bioresource Technology, 2023)

Bifacial perovskite solar cells: a universal component that goes beyond albedo utilization - Shan Gan; Haoxuan Sun; Chen Li; Da Dou; Liang Li (Science Bulletin, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

4-Methylbenzylidene camphor triggers estrogenic effects via the brain-liver-gonad axis in zebrafish larvae - Hongyi Xian; Zhiming Li; Rongyi Ye; Mingzhu Dai; Yu Feng; Ruobing Bai; Jie Guo; Xiliang Yan; Xingfen Yang; Da Chen; Zhenlie Huang (Environmental Pollution, 2023)

Lateral impact behaviour of post-fire steel-reinforced concrete-filled steel tubular members: Experiment and evaluation method - Sun-Hang Ji; Wen-Da Wang; Wensu Chen; Yan-Li Shi; Wei Xian (Engineering Structures, 2023)

The culprit for the declining performance of anaerobic reactors caused by calcification: Bioavailability deterioration - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Application of seaweed polysaccharide in bone tissue regeneration - Ye Jin; Qixuan Yu; Shuangyang Li; Tianli Chen; Da Liu (Frontiers in Marine Science, 2023)
Regeneration is a complex process influenced by many independent or combined factors, including inflammation, proliferation, and tissue remodeling. The ocean, the most extensive resource on Earth, is rich in Seaweed. With increasing research in recent years, researchers have discovered that seaweed polysaccharides have various pharmacological effects, including a particular efficacy in promoting bone tissue regeneration. However, the application of this material in the field of bone tissue engineering is very limited. However, there are few studies on the polysaccharide at home and abroad, and little is known about its potential application value in bone repair. In addition, the bioavailability of the seaweed polysaccharide is also low, and there are still many problems to be solved. For example, the ease of solubility of fucoidan in water is a key issue that restricts its practical application. In this review, we summarize the applications and mechanisms of seaweed polysaccharides in bone healing. We also propose to combine seaweed polysaccharides with novel technologies through different types of preparations, hydrogels, scaffolds, and 3D printing to improve their use in tissue healing and regeneration.

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Distinct variations and mechanisms for terrestrial OC 14C-ages in the Eastern China marginal sea sediments since the last deglaciation - Mengna Chen; Da-Wei Li; Hailong Zhang; Zicheng Wang; Meixun Zhao (Quaternary Science Reviews, 2023)

Legume-specific SnRK1 promotes malate supply to bacteroids for symbiotic nitrogen fixation - Da Guo; Peng Liu; Qianwen Liu; Lihua Zheng; Sikai Liu; Chen Shen; Li Liu; Shasha Fan; Nan Li; Jiangli Dong; Tao Wang (Molecular Plant, 2023)

Enhancement of hydrotreating activity of oil-soluble CoMo6 heteropolyacid for 4,6-dimethyldibenzothiophene and vacuum residue by controlling sulfurization degree - Qingyang Li; Zhengting Xiao; Hongchuan Xin; Guangci Li; Da Wang; Chao Feng; Xuebing Li; Song Chen; Keng H. Chung (Chemical Engineering Journal, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Towards intensified preservation technology of anammox granular sludge: Insights into the role of energy support - Chao Pan; Wenji Li; Dongdong Xu; Wenda Chen; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Toxicity and potential underlying mechanism of Karenia selliformis to the fish Oryzias melastigma - Qin-yuan Liu; Zi-min Chen; Da-wei Li; Ai-feng Li; Ying Ji; Hong-ye Li; Wei-dong Yang (Aquatic Toxicology, 2023)

Characterization of sandalwood (E,E)-α-farnesene synthase whose overexpression enhances cold tolerance through jasmonic acid biosynthesis and signaling in Arabidopsis - Xinhua Zhang; Xiaohong Chen; Jaime A. Teixeira da Silva; Ting Zhang; Yuping Xiong; Yuan Li; Yunfei Yuan; Xiaoping Pan; Guohua Ma (Planta, 2023)

RNA-seq analysis reveals an immunomodulatory peptide from highland barley activating RAW264.7 macrophages via TNF/NF-κB signaling pathway - Yan Liu; Xin Chen; Jia-Yi Yang; Zhi Jian Guo; Qin Wu; Li-Da Zhang; Xuan-Wei Zhou (Functional & Integrative Genomics, 2023)

Occurrence and screening- flotation separation for the beneficiation of rare earth elements and yttrium (REY) in core sediments from the Pacific Ocean - Anni Ouyang; Wenliang Xiong; Xiaoyu Li; Da Chen; Lijun Zhang; Peng Jiang (Marine Geology, 2023)

Industrial symbiosis promoting material exchanges in Ulan Buh Demonstration Eco-industrial Park: A multi-objective MILP model - Hao Yu; Lin Da; Yalun Li; Yanqiong Chen; Qingdan Geng; Zhibin Jia; Yun Zhang; Jinhua Li; Caixia Gao (Journal of Cleaner Production, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Two new diterpenoids from the rhizomes of Zingiber officinale - Mi Zhou; Ting Li; Chen Zeng; Da-bo Pan; Hai-bo Li; Yang Yu (Natural Product Research, 2023)

Discovery of a substance that enhances the immune response in Litopenaeus vannamei against WSSV: Baicalein, a major component of Scutellaria baicalensis - Li-Peng Shan; Ling Hu; Xu Zhang; Da-Wei Song; Yang Hu; Lei Liu; Jiong Chen (Aquaculture, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Effect of Clostridium butyricum on intestinal microbiota and resistance to Vibrio alginolyticus of Penaeus vannamei - Chen Wang; Peng-Fei Li; Da-Gang Hu; Hui Wang (Fish & Shellfish Immunology, 2023)

Positive response of host root-associated bacterial community and soil nutrients to inhibitory parasitism of dodder - Wen Luo; Yuanli Li; Yidan Jia; Yifu Chen; Da Li; Ruiping Luo; Gehong Wei; Minxia Chou; Weimin Chen (Plant and Soil, 2023)

Strength Assessment of Cement-Based Materials under Marine Conditions Subjected to Sulfate and Chloride Attack Based on Ion Distributions - Shagang Li; Xiaotong Yu; Wentao Zhou; Yingdi Liao; Da Chen (Journal of Marine Science and Engineering, 2023)
Sulfate and chloride in the marine environment threaten the lifespan of concrete structures. Predicting the strength of concrete under different degrees of ion erosion is essential for marine structure design and maintenance. In this paper, a novel method was developed to predict the compressive strength evolution due to sulfate and chloride attack. The degradation and ion diffusion behavior of cement-based materials was investigated by analyzing the visual appearance, compressive strength, porosity, and ion distributions of mortar soaked in sulfate and chloride solutions with different concentrations. The damage degree was observed to increase with sulfate concentration and decrease with chloride concentration. Additionally, it was discovered that chloride and sulfate ions inhibited the diffusion of each other, and a higher concentration resulted in a more substantial inhibition effect. The total effective sulfate and chloride intrusions were proposed to describe the erosion degree of mortar based on the evaluation of the ion distributions with Fick’s second law. A compressive strength assessment method was established based on the analysis of the correlation between the strength contribution of sulfate reaction and the total effective chloride and sulfate intrusions. This method exhibits the potential for estimating the concrete strength of actual marine structures damaged by sulfate and chloride with accelerated laboratory tests.

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Construction of graphene quantum dots ratiometric fluorescent probe by intermolecular electron transfer effect for intelligent and real-time visual detection of ofloxacin and its L-isomer in daily drink - Changxing Wang; Feifei Qin; Siyuan Tang; Xiameng Li; Tingting Li; Guoqiang Guo; Chenjie Gu; Xu Wang; Da Chen (Food Chemistry, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Control release of α-mangostin by a novel dual-polysaccharides delivery system for colitis treatment under simulated gastrointestinal conditions - Jialong Li; Cuicui Zeng; Qiqi Huang; Ming-Ming Zheng; Jing Chen; Da Ma (Food Bioscience, 2023)

Activated cascade effect for dual-mode ratiometric and smartphone-assisted visual detection of curcumin and F− based on nitrogen-doped carbon dots - Siyuan Tang; Yiru Wang; Guoqiang Guo; Tingting Li; Haoming Xing; Houwen Hu; Xuan Leng; Chenjie Gu; Da Chen (Science of The Total Environment, 2023)

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Multiple ocean oxygenation events during the Ediacaran Period: Mo isotope evidence from the Nanhua Basin, South China - Lin Yuan; Ying Zhou; Xi Chen; Maoyan Zhu; Simon W. Poulton; Zheyu Tian; Da Li; Matthew Thirlwall; Graham A. Shields (Precambrian Research, 2023)

Efficient degradation of 2,3,5-trimethylpyrazine by catalytic ozonation over MnOx supported on biochar derived from waste tea leaves - Yinning He; Yi Chen; Jinzhe Li; Da Wang; Shuang Song; Feilong Dong; Zhiqiao He (Chemical Engineering Journal, 2023)

Environmental chemicals and adverse pregnancy outcomes: Placenta as a target and possible driver of pre- and postnatal effects - Jing Li; Adrian Covaci; Da Chen (Critical Reviews in Environmental Science and Technology, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Axially chiral TADF-active materials with π-extended acceptors for highly efficient circularly polarized electroluminescence - Ke-Ke Tan; Da-Wei Zhang; Wen-Long Zhao; Meng Li; Chuan-Feng Chen (Chemical Engineering Journal, 2023)

ZnO microrods sandwiched between layered CNF matrix: Fabrication, stress transfer, and mechanical properties - Ying Gao; Bin Chen; Marcus Vinícius Tavares da Costa; Hongqi Dai; Farsa Ram; Yuanyuan Li (Carbohydrate Polymers, 2023)

High density polyethylene (HDPE) and thermoplastic polyurethane (TPU) wristbands as personal passive samplers monitoring per- and polyfluoroalkyl substances (PFASs) exposure to postgraduate students - Yun Deng; Fei Wang; Liangying Liu; Da Chen; Ying Guo; Zhe Li (Journal of Hazardous Materials, 2023)

The remarkable enhancement of photo-stability and antioxidant protection of lutein coupled with carbon-dot - Da-jian Jv; Tian-hao Ji; Zhemi Xu; Ao Li; Zhong-yi Chen (Food Chemistry, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Molecular mechanism of di-n-butyl phthalate promotion of bladder cancer development - En-Hui Li; Bai-Hui Xu; Hai-Bin Wei; Yu-Chen Bai; Qi Zhang; Wei-Wen Yu; Zhi-Hui Xu; Xiao-Long Qi; Da-Hong Zhang; Heng Wang (Toxicology in Vitro, 2023)

Two new lignans from the herbaceous stems of Ephedra intermedia - Xi-Ling Fan; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Ying-Jie Ren; Xin-Yi Ma; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Holdup of sub-granules towards enhanced production of anammox sludge in a dual circulation sludge bed reactor - Dongdong Xu; Wenda Chen; Chao Pan; Wenji Li; Leiyan Guo; Da Kang; Ping Zheng; Baolan Hu; Meng Zhang (Chemical Engineering Journal, 2023)

Subnano-sized tellurium@nitrogen/phosphorus co-doped carbon nanofibers as anode for potassium-based dual-ion batteries - Dandan Yu; Wen Luo; Hongfei Gu; Kexin Li; Junhui Liang; Huayu Chen; Qingsheng Wang; Da Chen; Yuexiang Huang; Pavel Novikov; Anatoliy A. Popovich; Laishun Qin (Chemical Engineering Journal, 2023)

Pyrite trace element and S-Pb isotopic evidence for contrasting sources of metals and ligands during superimposed hydrothermal events in the Dongping gold deposit, North China - Huan Li; Da-Peng Zhu; Thomas J. Algeo; Ming Li; Wei-Cheng Jiang; She-Fa Chen; Safiyanu Muhammad Elatikpo (Mineralium Deposita, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Correction to: Shoot organogenesis and plant regeneration from leaf and petiole explants of Corydalis saxicola Bunting - Jinhui Pang; Yuping Xiong; Yujie Zeng; Xiaohong Chen; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2023)

Shoot organogenesis and plant regeneration from leaf and petiole explants of Corydalis saxicola Bunting - Jinhui Pang; Yuping Xiong; Yujie Zeng; Xiaohong Chen; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2023)
Corydalis saxicola Bunting, a medicinal herb known for alkaloids, grows mainly in Guizhou province and northwest Guangxi province of China. In this study, for the first time for this plant, an efficient adventitious shoot proliferation and regeneration system via shoot organogenesis from leaf and petiole explants was established. Cytokinins, including 6-benzyladenine (BA) and thidiazuron (TDZ), induced callus and then shoot organogenesis. Most adventitious shoots were induced from leaf explants on Murashige and Skoog (MS) medium (pH 6.5) supplemented with 2.0 µM BA and 0.5 µM α-naphthaleneacetic acid (NAA). This medium was also optimal for shoot proliferation. The rooting ½MS medium was supplemented with 1.0 µM indole-3-butyric acid (IBA) and 0.2 µM NAA; 95.7% of shoots induced roots within 30 d and 91% of plantlets survived on a peat:vermiculite (1:1, v:v) substrate after 90 d.

A cDNA-based reverse genetics system for feline calicivirus identifies the 3′ untranslated region as an essential element for viral replication - Jie Cheng; Aoxing Tang; Jing Chen; Da Zhang; Chunchun Meng; Chuanfeng Li; Hulai Wei; Guangqing Liu (Archives of Virology, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Evaluation on prevention and treatment of cuminaldehyde in culture of shrimp against white spot syndrome virus - Xu Zhang; Li-Hua Hu; Da-Wei Song; Yang Hu; Jiong Chen (Aquaculture, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Phytoplankton productivity and community structure changes in the middle Okinawa Trough since the last deglaciation - Mengna Chen; Da-Wei Li; Li Li; Gui'e Jin; Guangxue Li; Jishang Xu; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Energy transfer mediated rapid and visual discrimination of tetracyclines and quercetin in food by using N, Cu Co-doped carbon dots - Tingting Li; Guoqiang Guo; Haoming Xing; Yiru Wang; Xinyu Luo; Linfan Wang; Chenjie Gu; Yafei Hou; Da Chen (Analytica Chimica Acta, 2023)

Transcriptome analysis of knockout mutants of rice seed dormancy gene OsVP1 and Sdr4 - Wen-Qiang Chen; Da-Pu Liu; Zhi-Xin Li; Kai Chen; Ju Luo; Jian-Long Xu (Plant Cell Reports, 2022)

Correction to: Protective effects of fowl‑origin cadmium‑tolerant lactobacillus against sub‑chronic cadmium‑induced toxicity in chickens - Da‑Wei Chen; Hui‑Jia Li; YinYin Liu; Li‑Na Ma; Jun‑Hua Pu; JunXian Lu; Xiu‑Jun Tang; Yu‑shi Gao (Environmental Science and Pollution Research, 2022)

Protective effects of fowl-origin cadmium-tolerant lactobacillus against sub-chronic cadmium-induced toxicity in chickens - Da-Wei Chen; Hui-Jia Li; YinYin Liu; Li-Na Ma; Jun-Hua Pu; JunXian Lu; Xiu-Jun Tang; Yu-shi Gao (Environmental Science and Pollution Research, 2022)

Risk of thyroid cancer and benign nodules associated with exposure to parabens among Chinese adults in Wuhan, China - Nan-Xin Wu; Lang-Jing Deng; Feng Xiong; Jin-Ying Xie; Xiao-Jie Li; Qiang Zeng; Jia-Chen Sun; Da Chen; Pan Yang (Environmental Science and Pollution Research, 2022)

A single-cell survey unveils cellular heterogeneity and sensitive responses in mouse cortices induced by oral exposure to triphenyl phosphate - Di Ji; Yuejin Yu; Qicheng Zhu; Xianjie Li; Xiali Zhong; Zhuyi Zhang; Weijian Ke; Congying Niu; Can Wang; Jingwei Wu; Da Chen; Maoyong Song; et al. (Archives of Toxicology, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Shoot organogenesis from leaf and stem explants of Heliotropium foertherianum Diane and Hilger - Xincheng Yu; Xiaohong Chen; Yuping Xiong; Yujie Zeng; Zhenpeng Wei; Jinhui Pang; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2022)

Influences of the 1855 AD Huanghe (Yellow River) Relocation on Sedimentary Organic Carbon Burial in the Southern Yellow Sea - Jianying Liu; Da-Wei Li; Yang Ding; Tiantian Ge; Weifang Chen; Chih-An Huh; Meixun Zhao (Frontiers in Marine Science, 2022)
The Huanghe (Yellow River) supplies large amount of sediments and terrestrial organic carbon (OC) to the eastern Chinese marginal seas. A relocation of the Huanghe outlet from the southern Yellow Sea (YS) to the Bohai Sea occurred in 1855 AD, however, detailed knowledge about the impact of this relocation on sedimentary source and OC burial in Chinese marginal seas is still critically lacking. In this study, we present total OC content and its isotope (δ 13 C), along with bulk total organic carbon (TOC)/total nitrogen (TN) molar ratio and lipid biomarker contents, in a sediment core HH12 from the southern YS with sediment age spanning the last 300 years. We find that TOC and terrestrial lipid biomarker mass accumulation rates were lower between 1855 AD and 1950 AD than that prior to 1855 AD in core HH12; and in accordance, both TOC/TN ratio and δ 13 C records indicate a gradual decrease of terrigenous source contributions to sedimentary OC. This suggests that the relocation of the Huanghe outlet reduced the transport of terrestrial OC to the southern YS. However, the δ 13 C record also indicates a relative increase of terrestrial OC contribution to sedimentary OC after 1950 AD, and the most likely explanation is increased contributions from the old Huanghe delta erosion and Korean rivers. Future studies should focus on better constraining the variations of terrestrial and marine endmembers with δ 13 C and Δ 14 C analyses of specific biomarkers to examine these linkages.

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Effect of Carbonation and Drying-Wetting Cycles on Chloride Diffusion Behavior of Coral Aggregate Seawater Concrete - Bo Da; Yipeng Li; Hongfa Yu; Haiyan Ma; Haoyu Chen; Xuemei Dou; Zhangyu Wu (Journal of Ocean University of China, 2022)

HMGB1-RAGE Pathway Contributes to the Abnormal Migration of Endogenous Subventricular Zone Neural Progenitors in an Experimental Model of Focal Microgyria - Yi-Wen Mei; Tian-Lan Huang; Xin Chen; Si-Xun Yu; Jie Li; Zhi Zhang; Yang He; Da-qing Guo; Hai-Feng Shu (Journal of Molecular Neuroscience, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

The test and fitting analysis of Hunan clay soil–water characteristic curve in full suction range - Gaoliang Tao; Kai Gu; Chuheng Zhong; Yangyang Chen; Da Lei; Ziyue Li (Arabian Journal of Geosciences, 2021)

Synthesis of pyrazole-4-carboxamides as potential fungicide candidates - Cuntao Dong; Wei Gao; Xiaotian Li; Susu Sun; Jingqian Huo; Yanen Wang; Da Ren; Jinlin Zhang; Lai Chen (Molecular Diversity, 2021)

Time-dependent damage mechanism of rock deterioration under freeze–thaw cycles linked to alpine hazards - Guoqing Chen; Yi Wan; Yang Li; XiangJun Pei; Da Huang (Natural Hazards, 2021)

Neuroprotective triterpene saponins from the leaves of Panax notoginseng - Ji-Wu Huang; Yi-Qian Du; Chuang-Jun Li; Jing-Zhi Yang; Jie Ma; Ying-Da Zang; Nai-Hong Chen; Dong-Ming Zhang (Natural Product Research, 2021)

A DEM-Based Approach for Modeling the Damage of Rock Under Freeze–Thaw Cycles - Tantan Zhu; Jianxun Chen; Da Huang; Yanbin Luo; Yao Li; Longfei Xu (Rock Mechanics and Rock Engineering, 2021)

Multiple diversity facets of crucial microbial groups in biological soil crusts promote soil multifunctionality - Hua Li; Youxin Chen; Gongliang Yu; Federico Rossi; Da Huo; Roberto De Philippis; Xiaoli Cheng; Weibo Wang; Renhui Li (Global Ecology and Biogeography, 2021)
Aim Microbial diversity is one of the most important factors for maintaining the performance of multiple functions in soils (multifunctionality). However, existing studies typically consider the taxonomic richness or Shannon diversity of the entire community. We know little about the connection network of taxonomic and phylogenetic facets of diversity and their collective impact on multifunctionality. In this study, the linkages of effects of diversity within functional groups were disentangled in drylands. Location The central Tibetan Plateau. Time period Present. Major taxa studied Phototrophs and diazotrophs (mainly cyanobacteria). Methods Given the carbon‐ and nitrogen‐limited nature of drylands, we conducted a high‐throughput sequencing of C/N‐fixing functional groups from biocrusts and evaluated multiple facets of diversity (i.e., richness, evenness and phylogeny‐related trait dissimilarity), together with seven crucial variables of soil functioning to calculate multifunctionality. The relationships between multifaceted diversity and abundance with individual functions and multifunctionality were validated by a set of solid statistical analyses. Results We found that the integrated biodiversity index was a stronger predictor of multifunctionality than richness. The divergent performance of different facets of diversity determined the idiosyncratic effect of each functional group on soil multifunctionality. Moreover, the evaluation of functional significance at the species level gave important clues on the trade‐offs and redundancy in each functional group, explaining the distinct patterns of effects of diversity. Richness was the dominant factor for diazotrophs to maximize multifunctionality, whereas phylogenetic dissimilarity was the essential one for phototrophs. Main conclusions Our study demonstrated that multiple facets of diversity should be considered when assessing the effects of biodiversity. In contrast to the community level, within‐functional group measures might adequately capture the features of diversity that are most correlated with soil multifunctionality. Our results provide a perspective to bridge the gap between taxonomic and trait‐based approaches for elucidating the biodiversity–ecosystem function relationship.

LncRNA FTX Promotes Colorectal Cancer Cells Migration and Invasion by miRNA-590-5p/RBPJ Axis - Guo-Qun Chen; Zhi-Ming Liao; Jiao Liu; Fang Li; Da Huang; Ya-Dong Zhou (Biochemical Genetics, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Stochastic processes shape the biogeographic variations in core bacterial communities between aerial and belowground compartments of common bean - Yang Liu; Da Li; Jiejun Qi; Ziheng Peng; Weimin Chen; Gehong Wei; Shuo Jiao (Environmental Microbiology, 2021)
Although studies of biogeography in soil bacterial communities have attracted considerable attention, the generality of these patterns along with assembly processes and underlying drivers is poorly understood in the inner tissues of plants. Plant tissues provide unique ecological habitats for microorganisms, which play an essential role in plant performance. Here, we compared core bacterial communities among five soil–plant associated compartments of common bean across five sampling sites in China. Neutral and null modelling consistently suggested that stochastic processes dominated the core community assembly processes and escalated from the belowground compartments to the inner tissues of aerial plant parts. The multiple distance‐decay relationships also varied and had flattened patterns in the stem endosphere, which were shaped by distinct environmental factors in each compartment. Coexistence patterns also varied in topological features, in addition with the sparsest networks in the stem endosphere resulted from the interaction with the stochastic processes. This study considerably expanded our understanding of various biogeographic patterns, assembly processes, and the underlying mechanisms of core bacterial communities between aerial and belowground compartments of common bean. That will provide a scientific basis for the reasonable regulation of core bacterial consortia to get better plant performance.

The Complete Genome Sequence of a Bacterial Strain with High Alkalic Xylanase Activity Isolated from the Sludge Near a Papermill - Si Chen; Hao Feng; Xin Li; Hong-jun Chao; Jing Wu; Jun Liu; Wen-jun Zhu; Da-zhong Yan (Current Microbiology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Geochemical features and potential environmental implications of heavy metals in mining-impacted sediments, south China - Bo Yan; Da-Mao Xu; Tao Chen; ZiAng Yan; Li-li Li (Environmental Science and Pollution Research, 2020)

Development of a rapid and sensitive europium (III) chelate microparticle-based lateral flow test strip for the detection and epidemiological surveillance of porcine epidemic diarrhea virus - Jianbo Liu; Hongyan Shi; Guangyi Cong; Jianfei Chen; Xin Zhang; Da Shi; Liyan Cao; Xiaobo Wang; Jialin Zhang; Zhaoyang Ji; Zhaoyang Jing; Li Feng (Archives of Virology, 2020)

Development of an indirect ELISA for detecting porcine deltacoronavirus IgA antibodies - Manman Lu; Qiuge Liu; Xiaobo Wang; Jialin Zhang; Xin Zhang; Da Shi; Jianbo Liu; Hongyan Shi; Jianfei Chen; Li Feng (Archives of Virology, 2020)

Multifunctionality of biocrusts is positively predicted by network topologies consistent with interspecies facilitation - Hua Li; Da Huo; Weibo Wang; Youxin Chen; Xiaoli Cheng; Gongliang Yu; Renhui Li (Molecular Ecology, 2020)
The potential of biodiversity loss to impair the delivery of ecosystem services has motived ecologists to better understand the relationship between biodiversity and ecosystem functioning. Although increasing evidence underlines the collective contribution of different biodiversity components on the simultaneous performance of multiple functions (multifunctionality), we know little about the trade‐offs between individual diversity effects and the extent to which they determine multifunctionality differentially. Here, at a subcontinental scale of 62 dryland sites, we show in phototrophic microbiota of biological soil crusts (biocrusts) that, whereas richness alone is unable to guarantee the maxima of multifunctional performance, interspecies facilitation and compositional identity are particularly stronger but often neglected predictors. The inconsistent effects of different biodiversity components imply that soil multifunctionality can be lost despite certain species remaining present. Moreover, we reveal a significant empirical association between species functional importance and its topological feature in co‐occurrence networks, indicating a functional signal of species interaction. Nevertheless, abundant species tend to isolate and merely interact within small topological structures, but rare species were tightly connected in complicated network modules. Our findings suggest that abundant and rare species of soil phototrophs exhibit distinct functional relevance. These results give a comprehensive view of how soil constructive species drive multifunctionality in biocrusts and ultimately promote a deeper understanding of the consequences of biodiversity loss in real‐world ecosystems.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

An efficient micropropagation protocol for Metasequoia glyptostroboides Hu et Cheng from shoot segments of 2-year-old trees - Yuping Xiong; Shuangyan Chen; Beiyi Guo; Meiyun Niu; Xinhua Zhang; Yuan Li; Kunlin Wu; Feng Zheng; Jaime A. Teixeira da Silva; Songjun Zeng; Guohua Ma (Trees, 2020)

Correction to: NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Tissue-Specific Monoallelic Expression of Bovine AXL is Associated with DNA Methylation of Promoter DMR - Da Xu; Guannan Wang; Junliang Li; Cui Zhang; Weina Chen; Dongjie Li; Shijie Li (Biochemical Genetics, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Orange and red carotenoid proteins are involved in the adaptation of the terrestrial cyanobacterium Nostoc flagelliforme to desiccation - Yi-Wen Yang; Yan-Chao Yin; Zheng-Ke Li; Da Huang; Jin-Long Shang; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Applications of Raman spectroscopic techniques for quality and safety evaluation of milk: A review of recent developments - Huirong He; Da-Wen Sun; Hongbin Pu; Lijun Chen; Li Lin (Critical Reviews in Food Science and Nutrition, 2019)

Influences of zinc oxide nanoparticles on Allium cepa root cells and the primary cause of phytotoxicity - Zhiqiang Sun; Tiantian Xiong; Ting Zhang; Nanfang Wang; Da Chen; Shaoshan Li (Ecotoxicology, 2019)

LINC24065 is a monoallelically expressed long intergenic noncoding RNA located in the cattle DLK1–DIO3 cluster - Cui Zhang; Da Xu; Weina Chen; Junliang Li; Qinghua Gao; Shijie Li (Journal of Genetics, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Whole-exome sequencing reveals SALL4 variants in premature ovarian insufficiency: an update on genotype–phenotype correlations - Qiqi Wang; Da Li; Baozhu Cai; Qing Chen; Caihua Li; Yanhua Wu; Li Jin; Xiuxia Wang; Xiaojin Zhang; Feng Zhang (Human Genetics, 2019)

Spatial distribution and environmental implications of heavy metals in typical lead (Pb)-zinc (Zn) mine tailings impoundments in Guangdong Province, South China - Tao Chen; Chang Lei; Bo Yan; Li-li Li; Da-mao Xu; Guang-Guo Ying (Environmental Science and Pollution Research, 2018)

Polymorphic Imprinting of SLC38A4 Gene in Bovine Placenta - Da Xu; Cui Zhang; Junliang Li; Guannan Wang; Weina Chen; Dongjie Li; Shijie Li (Biochemical Genetics, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Molecular detection of microbial communities associated with Microcystis vs Synechococcus dominated waters in Tianjin, China - Da Huo; Youxin Chen; Ping Liu; Yiming Li; Zhiyi Qiao; Renhui Li (Journal of Oceanology and Limnology, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Quantitative proteomics of pomegranate varieties with contrasting seed hardness during seed development stages - Juan Niu; Da Cao; Haoxian Li; Hui Xue; Lina Chen; Beibei Liu; Shangyin Cao (Tree Genetics & Genomes, 2018)

Detection and complete genome characteristics of Posavirus 1 from pigs in China - Jianfei Chen; Manman Lu; Tianxin Ma; Liyan Cao; Xiangdong Zhu; Xin Zhang; Da Shi; Hongyan Shi; Jianbo Liu; Li Feng (Virus Genes, 2018)

Metaproteomics reveals major microbial players and their metabolic activities during the blooming period of a marine dinoflagellate Prorocentrum donghaiense - Dong‐Xu Li; Hao Zhang; Xiao‐Huang Chen; Zhang‐Xian Xie; Yong Zhang; Shu‐Feng Zhang; Lin Lin; Feng Chen; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Interactions between bacteria and phytoplankton during bloom events are essential for both partners, which impacts their physiology, alters ambient chemistry and shapes ecosystem diversity. Here, we investigated the community structure and metabolic activities of free‐living bacterioplankton in different blooming phases of a dinoflagellate Prorocentrum donghaiense using a metaproteomic approach. The Fibrobacteres ‐ Chlorobi ‐ Bacteroidetes group, Rhodobacteraceae , SAR11 and SAR86 clades contributed largely to the bacterial community in the middle‐blooming phase while the Pseudoalteromonadaceae exclusively dominated in the late‐blooming phase. Transporters and membrane proteins, especially TonB‐dependent receptors were highly abundant in both blooming phases. Proteins involved in carbon metabolism, energy metabolism and stress response were frequently detected in the middle‐blooming phase while proteins participating in proteolysis and central carbon metabolism were abundant in the late‐blooming phase. Beta‐glucosidase with putative algicidal capability was identified from the Pseudoalteromonadaceae only in the late‐blooming phase, suggesting an active role of this group in lysing P . donghaiense cells. Our results indicated that diverse substrate utilization strategies and different capabilities for environmental adaptation among bacteria shaped their distinct niches in different bloom phases, and certain bacterial species from the Pseudoalteromonadaceae might be crucial for the termination of a dinoflagellate bloom.

Helpers of the Giant Babax cheat for an immediate reward when they provision the brood - Li-Qing Fan; Xin-Wei Da; Juan-Juan Luo; Li-Li Xian; Guo-Liang Chen; Bo Du (Journal of Ornithology, 2018)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

The first successful report of the in vitro life cycle of Chinese Leishmania: the in vitro conversion of Leishmania amastigotes has been raised to 94% by testing 216 culture medium compound - Jiao Li; Zhi-Wan Zheng; Gayathri Natarajan; Qi-Wei Chen; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2017)
Chinese

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Valuation of debris flow mitigation measures in tourist towns: a case study on Hongchun gully in southwest China - Ming-li Chen; Gui-sheng Hu; Ning-sheng Chen; Cun-yao Zhao; Song-jiang Zhao; Da-wei Han (Journal of Mountain Science, 2016)

Comparative genomic analysis of Lactobacillus plantarum ZJ316 reveals its genetic adaptation and potential probiotic profiles - Ping Li; Xuan Li; Qing Gu; Xiu-yu Lou; Xiao-mei Zhang; Da-feng Song; Chen Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Application of in-house virtual protein database performed in genomic-proteomic combined research on heavy-metal stressed onion roots - Chanjuan Ning; Rong Qin; Da Chen; Lars Olof Björn; Shaoshan Li (Biotechnology Letters, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Cytotoxic monoterpenoid indole alkaloids isolated from the barks of Voacanga africana Staph. - Hong-Mei Chen; Yu-Ting Yang; Hong-Xiang Li; Zhi-Xing Cao; Xiao-Mei Dan; Ling Mei; Da-Le Guo; Chuan-Xia Song; Yu Dai; Jia Hu; Yun Deng (Natural Product Research, 2016)

Genomic and physiological analysis reveals versatile metabolic capacity of deep-sea Photobacterium phosphoreum ANT-2200 - Sheng-Da Zhang; Claire-Lise Santini; Wei-Jia Zhang; Valérie Barbe; Sophie Mangenot; Charlotte Guyomar; Marc Garel; Hai-Tao Chen; Xue-Gong Li; Qun-Jian Yin; Yuan Zhao; Jean Armengaud; et al. (Extremophiles, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

The marine redox change and nitrogen cycle in the Early Cryogenian interglacial time: Evidence from nitrogen isotopes and Mo contents of the basal Datangpo Formation, northeastern Guizhou, South China - Wei Wei; Dan Wang; Da Li; Hongfei Ling; Xi Chen; Guangyi Wei; Feifei Zhang; Xiangkun Zhu; Bin Yan (Journal of Earth Science, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Immunogenicity and antigenic relationships among spike proteins of porcine epidemic diarrhea virus subtypes G1 and G2 - Xiaobo Wang; Jianfei Chen; Da Shi; Hongyan Shi; Xin Zhang; Jing Yuan; Shibo Jiang; Li Feng (Archives of Virology, 2016)

Immunogenicity and antigenic relationships among spike proteins of porcine epidemic diarrhea virus subtypes G1 and G2 - Xiaobo Wang; Jianfei Chen; Da Shi; Hongyan Shi; Xin Zhang; Jing Yuan; Shibo Jiang; Li Feng (Archives of Virology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Protective effect of low dose gadolinium chloride against isoproterenol-induced myocardial injury in rat - Yuan-Yuan Zheng; Hai-Hong Zhang; Xin-Xin Yan; Min Chen; Tian-Yu Qi; Lan-E Zhang; Da-Li Luo (Apoptosis, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Sublethal and hormesis effects of imidacloprid on the soybean aphid Aphis glycines - Yanyan Qu; Da Xiao; Jinyu Li; Zhou Chen; Antonio Biondi; Nicolas Desneux; Xiwu Gao; Dunlun Song (Ecotoxicology, 2015)

Impact of LPS-Induced Cardiomyoblast Cell Apoptosis Inhibited by Earthworm Extracts - Ping-Chun Li; Yun-Chen Tien; Cecilia Hsuan Day; Peiying Pai; Wei-Wen Kuo; Tung-Sheng Chen; Chia-Hua Kuo; Chang-Hai Tsai; Da-Tong Ju; Chih-Yang Huang (Cardiovascular Toxicology, 2015)

The prevalence of heifer mastitis and its associated risk factors in Huanggang, Central China - Feng Li Yang; Chen Shen; Bao Xiang He; Yu Ying Yang; Da Chun Gong; Xiao Shan Li (Tropical Animal Health and Production, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

N-3 polyunsaturated fatty acids intake and risk of colorectal cancer: meta-analysis of prospective studies - Guo-Chong Chen; Li-Qiang Qin; Da-Bing Lu; Tie-Mei Han; Yan Zheng; Guo-Zhang Xu; Xiao-Huai Wang (Cancer Causes & Control, 2015)

Management of differentiated thyroid carcinoma with bone metastasis: a case report and review of the Chinese literature - Wei-dong Zhang; Da-ren Liu; Cheng-cheng Feng; Chuan-biao Zhou; Chen-ni Zhan; Ri-sheng Que; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

HER-2 overexpression and survival in colorectal cancer: a meta-analysis - Chao Li; Da-ren Liu; Long-yun Ye; Ling-na Huang; Sanjay Jaiswal; Xiao-wen Li; Hou-hong Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Identification, characterization and feeding response of peptide YYb (PYYb) gene in grass carp (Ctenopharyngodon idellus) - Yong Chen; Narayan Prasad Pandit; Jianjun Fu; Da Li; Jiale Li (Fish Physiology and Biochemistry, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Characterization and cross-species amplification of 11 polymorphic microsatellite loci in Liobagrus marginatoides - Xiang-Yang Jia; Ying-Wen Li; Deng-Qiang Wang; Hui-Wu Tian; Bin Tu; Da-Qing Chen (Conservation Genetics Resources, 2013)

Multiplex microsatellite PCR sets for parentage assignment of grass carp (Ctenopharyngodon idella) - Jianjun Fu; Yubang Shen; Xiaoyan Xu; Yong Chen; Da Li; Jiale Li (Aquaculture International, 2013)

Molecular characterization of a porcine kobuvirus variant strain in China - Da Shi; Sha Zhang; Jianfei Chen; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Systematic review of laparoscopy-assisted versus open gastrectomy for advanced gastric cancer - Long-yun Ye; Da-ren Liu; Chao Li; Xiao-wen Li; Ling-na Huang; Sheng Ye; Yi-xiong Zheng; Li Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic variation of nucleocapsid genes of porcine epidemic diarrhea virus field strains in China - Jianfei Chen; Xiaozhen Liu; Hongwu Lang; Zhongtian Wang; Da Shi; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Genetic transformation of Populus tomentosa to improve salt tolerance - Ningxia Du; Xin Liu; Yun Li; Shouyi Chen; Jinsong Zhang; Da Ha; Wenguang Deng; Chunkui Sun; Yingzhi Zhang; Paula M. Pijut (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Adaptive evolution of context-dependent style curvature in some species of the Malvaceae: a molecular phylogenetic approach - Cheng-Jiang Ruan; Shi-Chao Chen; Qun Li; Jaime A. Teixeira da Silva (Plant Systematics and Evolution, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development - Ai Hua Chen; Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Computational investigation of the Anti-HIV activity of Chinese medicinal formula Three-Huang Powder - Jack Z. Hu; Li Bai; Da-Gang Chen; Qi-Tai Xu; William M. Southerland (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Geographic substructure of Fusarium asiaticum isolates collected from barley in China - Zheng Zhang; Hao Zhang; Theo van der Lee; Wan-Quan Chen; Paul Arens; Jin Xu; Jing-Sheng Xu; Li-Jun Yang; Da-Zhao Yu; Cees Waalwijk; Jie Feng (European Journal of Plant Pathology, 2010)

Down-Regulation of Stat3 Decreases Invasion Activity and Induces Apoptosis of Human Glioma Cells - Fuxue Chen; Yaming Xu; Youqun Luo; Da Zheng; Yichao Song; Kangkang Yu; Hong Li; Li Zhang; Weiwei Zhong; Yonghua Ji (Journal of Molecular Neuroscience, 2010)

The effects of CYP2C9 and CYP2C19 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of glipizide in Chinese subjects - Bo Tan; Yi-Fan Zhang; Xiao-Yan Chen; Xiao-Hua Zhao; Guo-Xin Li; Da-Fang Zhong (European Journal of Clinical Pharmacology, 2010)

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes - Da Chun Chen; Jing Wang; Bo Wang; Sheng Chang Yang; Chong Xi Zhang; You Lan Zheng; Yan Li Li; Ning Wang; Ke Bing Yang; Mei Hong Xiu; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2009)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Mitochondrial functions on oocytes and preimplantation embryos - Li-ya Wang; Da-hui Wang; Xiang-yang Zou; Chen-ming Xu (Journal of Zhejiang University-SCIENCE B, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

The symbiosis phenotype and expression patterns of five nodule-specific genes of Astragalus sinicus under ammonium and salt stress conditions - Da-Song Chen; You-Guo Li; Jun-Chu Zhou (Plant Cell Reports, 2007)

Up-regulation interleukin-6 and interleukin-8 by activated protein C in lipopolysaccharide-treated human umbilical vein endothelial cells - Yi Li; Bin Du; Jia-qi Pan; De-chang Chen; Da-wei Liu (Journal of Zhejiang University-SCIENCE B, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Testifying the rice bacterial blight resistance gene xa5 by genetic complementation and further analyzing xa5 (Xa5) in comparison with its homolog TFIIAγ1 - Guang-Huai Jiang; Zhi-Hui Xia; Yong-Li Zhou; Jia Wan; Da-Yong Li; Run-Sheng Chen; Wen-Xue Zhai; Li-Huang Zhu (Molecular Genetics and Genomics, 2006)

DELIVERY AND STORAGE OF SINGLE EMBRYOS, SPERM, OR CELLS IN MICROGLASS CAPILLARIES - Min-Kang Wang; Ji-Long Liu; Li Lian; Da-Yuan Chen (In Vitro Cellular & Developmental Biology - Animal, 2002)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)

Ri-mediated transformation of Artemisia annua with a recombinant farnesyl diphosphate synthase gene for artemisinin production - Da-Hua Chen; Chang-Jun Liu; He-Chun Ye; Guo-Feng Li; Ben-Ye Liu; Yu-Ling Meng; Xiao-Ya Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)